Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T16:19:38+01:00
A) a+(a-b) = 2a+b
b) 2x-(x+4) = 2x-x-4=x-4
c) 7-(-x+6) = 7+x-6=x+1
d) -(x+4)+(x-5) = -x-4+x-5=-9
e) 1-(t+p)-(t-2) = 1-t-p-t+2=-p+3-2t
f) -(-y+2)+(-2y-4) = y-2-2y-4=-y-6
2 2 2
2010-02-16T16:21:22+01:00
A) a+(a-b)=a+a-b=2a-b
b) 2x-(x+4)=2x-x-4=x-4
c) 7-(-x+6)=7+x-6=x+1
d) -(x+4)+(x-5)=-x-4+x-5=-9
e) 1-(t+p)-(t-2)=1-t-p-t+2=-2t-p+3
f) -(-y+2)+(-2y-4)=y-2-2y-4=-y-6
1 3 1
2010-02-16T17:27:06+01:00
A) a+(a-b)=2a+b
b) 2x-(x+4)=2x-x-4= x-4
c) 7-(-x+6)= 7-(-1)*(-x+6)=7+x-6=x+1
d) -(x+4)+(x-5)=-1*(x+4)+(x-5)=-x-4+(x-5)=-9
e) 1-(t+p)-(t-2)=1-(-1)*(t+p)+(-t)+2=1-t-p+t+2=-p+3
f) -(-y+2)+(-2y-4)=-1*(-y+2)+(-2y-4)=y-2-2y+2=-y